Voting green: how natural disasters shape electoral outcomes in Brazil - Vieira, Thais Pilipczuk (2025)
Amid the increasing frequency of extreme weather events, this study examines the effect of natural disasters on electoral outcomes in Brazil, with a focus on support for pro-climate political platforms. Using data from the 2012, 2016, and 2020 Brazilian municipal elections matched with the Atlas of Natural Disasters, I employ a two-way fixed effects difference-in-differences approach to determine whether disaster-affected municipalities shifted political support in the 2020 elections. The results show that exposure to disasters consistently leads to a 4.3 percentage point increase in vote shares for left-leaning parties and a 4.7 percentage point reduction for right-leaning parties, historically associated with environmentally friendly and environmentally harmful stances, respectively. Moderately pro-climate parties also gain (3.3 points), though less consistently, while highly aligned environmental parties do not see significant increases. This paper presents novel subnational evidence from a fragmented political system, showing that natural disasters increase support for left-leaning parties, but not for explicitly environmental platforms. In a context of low programmatic clarity, voter behavior may be shaped more by broad ideological cues than by informed assessments of environmental agendas. This gap between support for the political left and meaningful backing for environmental action offers insights into the political and institutional challenges of advancing climate policy in developing democracies, especially at the local level, where disaster impacts and policy responses are most immediate.